Implementation of Islamic Education Values in Strengthening Pancasila-Based Character Education - Elok Aini Sulthon; Zuhri Fahruddin; Anzar Aquil (FALASIFA : Jurnal Studi Keislaman, 2025)
Pancasila contains values that align with Islamic teachings and should be instilled in elementary school through Islamic-based education . Research on the implementation of Pancasila in schools generally focuses on the learning process , while studies on the integration of Islamic values into Pancasila at NU Padomasan Elementary School are rare. The purpose of this study is to examine the implementation of Islamic values in Pancasila at Nahdlatul Ulama Padomasan Elementary School. This study uses a qualitative descriptive method with interviews with teachers , documentation on wall pictures, nameplates and curriculum , and observations at NU Padomasan Elementary School . Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Meanwhile, data validity was carried out by triangulation of sources. The results of this study indicate that the implementation of Islamic values in Pancasila at Nahdlatul Ulama Padomasan Elementary School is in the form of Khuluqiyah (Humanity) values through orphanage assistance activities every Muharram month, Good Friday social services, and condolences events . This study enriches the study of the integration of Islamic values in Pancasila at the elementary school level and becomes a reference for schools in developing habituation programs that instill human values and noble morals in students.